Caracterización del potencial exportador de cannabis medicinal que tiene Colombia, de acuerdo al contexto productivo y desarrollo económico del país entre el periodo 2016-2020 (2022)
The present monograph type research work aims to analyze the potential exporter of medicinal cannabis that Colombia has, according to the productive context and economic development of the country between the period 2016-2020. The context of the analysis was carried out, taking into account that the country has the geographical and productive conditions to carry out the process of commercialization and export of products derived from medicinal cannabis. The subject of study is based on the interest that arises not only from foreign trade, but also from the different contexts of the debate on cannabis and legal use from a medicinal perspective. The study was approached from a qualitative approach, deductive method and descriptive type. The results indicated a high production and export potential to several countries, of which the United States, Germany, the United Kingdom, Australia and Canada stand out, which has led to a great dynamic in the economic development of the regions. Concluding that the boom in this sector represents an investment opportunity and potential to reactivate the industry and at the same time promote rural and agricu